Risk Factors and Nomogram for Predicting Relapse Risk in Pediatric Neuromyelitis Optica Spectrum Disorders - Zhang, Shanchao; Qiao, Shan; Li, Haiyun; Zhang, Ranran; Wang, Meiling; Han, Tao; Liu, Xuewu; Wang, Yunshan (Frontiers in Immunology, 2022)
Background: Neuromyelitis optica spectrum disorders (NMOSDs) are attack-relapsing autoimmune inflammatory diseases of the central nervous system, which is characterized by the presence of serological aquaporin-4 (AQP4) antibody. However, this disorder was uncommon in children, and AQP4 antibody was often tested seronegative. However, some paediatric patients diagnosed as NMOSDs were tested myelin oligodendrocyte glycoprotein (MOG) antibody positive. The previous investigations of paediatric NMOSDs were usually focused on the clinical presentation, treatment responses, and long-term prognoses, but little is known about the risk factors predicting NMOSD relapse attack in a shorter time, especially, for Chinese children. Methods: We retrospectively identified 64 Chinese paediatric patients, including 39 positive for AQP4 antibody, 12 positive for MOG antibody and the rest negative for AQP4& MOG antibody. Independent risk factors predicting relapse in one-year follow up were extracted by multivariate regression analysis to establish a risk score model, and its performance evaluation was analyzed using receiver operating characteristic (ROC) curve, and the independent risk factors related to relapse manifestation were also explored through multivariate logistic analysis. A nomogram was generated to assess relapse attack in one-year follow-up. Thirty-five patients from 3 other centers formed an external cohort to validate this nomogram. Results: Four independent relapsed factors included discharge expanded disability status scale (EDSS) (p=0.017), mixed lesion onset (p=0.010), counts (≧1) of concomitant auto-antibodies (p=0.015) and maintenance therapy (tapering steroid with mycophenolate mofetil (MMF), p=0.009, tapering steroid with acetazolamide (AZA), p=0.045, tapering steroid only, p=0.025). The risk score modeled with these four factors was correlated with the likelihood of relapse in the primary cohort (AUC of 0.912) and the validation cohort (AUC of 0.846). Also, our nomogram exhibited accurate relapse estimate in the primary cohort, the validation cohort and the whole cohort, but also in the cohorts with AQP4 antibody positive/negative, and noticeably, it performed predictive risk improvement better than other factors in C-index, net reclassification improvement (NRI) and integrated discrimination improvement (IDI). Conclusions The risk score and nomogram could facilitate accurate prognosis of relapse risk in one-year follow-up for pediatric NMOSDs, and help clinicians provide personalized treatment to decrease the chance of relapse.